Massive open online networks for urban sensing: Design, deployment and challenges - TAN, Hwee Xian (Institutional Knowledge at Singapore Management University, 2015)
Recent escalating efforts to realize the vision of smart cities have become a global trend. Within such efforts, the setup of relevant infrastructure is necessary to enable scalable sensing and sense-making in urban environments. In this paper, we discuss the design and implementation of MOON - Massive Open Online Networks - to interconnect large-scale and diverse IoT devices to enable the acquisition of real-time sensing data. We describe the system architecture, and software protocols that form the components of MOON. In addition, we highlight the challenges in the deployment and management of such networks. These are derived through experiences gleaned from our extensive deployments of wireless infrastructure for large-scale, real-time sensing in both indoor and outdoor urban environments.